Food Safety on the Farm: Good Agricultural Practices and Good Handling Practices – Sanitary Facilities - Jessica A. Lepper; Renée Goodrich Schneider; Aswathy Sreedharan; Keith R. Schneider (EDIS)
The Food Safety on the Farm series is a collection that reviews the generally recognized principles of GAPs (good agricultural practices) as they relate to produce, primarily at the farm level and with a particular focus on fresh Florida crops and practices. This publication focuses on GAPs and GHPs (good handling practices) relating specifically to sanitary facilities. Written by Jessica A. Lepper, Aswathy Sreedharan, Renee M. Goodrich-Schneider, and Keith R. Schneider and published by the UF/IFAS Food Science and Human Nutrition Department, January 2018. http://edis.ifas.ufl.edu/fs159